2005
DOI: 10.1111/j.1467-9671.2005.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Spatial Distribution of DEM Error

Abstract: Assessment of a DEM's quality is usually undertaken by deriving a measure of DEM accuracy -how close the DEM's elevation values are to the true elevation. Measures such as Root Mean Squared Error and standard deviation of the error are frequently used. These measures summarise elevation errors in a DEM as a single value. A more detailed description of DEM accuracy would allow better understanding of DEM quality and the consequent uncertainty associated with using DEMs in analytical applications. The research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 19 publications
4
55
0
Order By: Relevance
“…In this case study, errors were positively correlated with terrain complexity (stdev), hillshading (shade) and with vegetation (NDVI). This confirms the previous results of Fisher (1998), Holmes et al (2000, p. 162) and Carlisle (2005). Finally, we showed that regressionkriging and auxiliary maps can be used to downscale existing coarse DEMs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this case study, errors were positively correlated with terrain complexity (stdev), hillshading (shade) and with vegetation (NDVI). This confirms the previous results of Fisher (1998), Holmes et al (2000, p. 162) and Carlisle (2005). Finally, we showed that regressionkriging and auxiliary maps can be used to downscale existing coarse DEMs.…”
Section: Discussionsupporting
confidence: 80%
“…The more robust, more sophisticated solutions are yet to be developed. The spatially correlated error component will also often correlate with the auxiliary information (Carlisle, 2005;Oksanen, 2006b). For example, in traditional cartography, it is known that the error of measuring elevations is primarily determined by the complexity of terrain (the slope factor), land cover (density of objects) and relative visibility (the shadow effect).…”
Section: Theorymentioning
confidence: 99%
“…However, adequate DEMs are not always available. It is also known that digital elevation data and other spatial data sets are subject to inherent errors (Carlisle, 2005). Furthermore, modelling karstic areas using a DEM is more difficult than modelling normal landscapes, due to sinks in the DEM that are usually explained as errors influenced by the rounding of the elevations to the nearest integer value (Tarboton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the advantages of topographical and geomorphological mapping of karstic landscapes with the assistance of GIS techniques, as well as a methodology for obtaining accurate stream nets. We investigate the hypothesis that the errors in a DEM are at least partly related to the nature of the terrain (Carlisle, 2005) and examine the relationship between the DEM errors and the LS factor values.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Wechsler (2007) the RMSE method sometimes does not calculate an accurate assessment of how precisely each grid in a DEM represents topographical features. To solve this issue, number of researchers proposed spatial simulation methods for assessing the uncertainty of elevation estimates in each DEMs grid (Holmes et al, 2000;Carlisle, 2005;Wechsler and Kroll, 2006;Abd Aziz et al, 2012). The spatial simulation process analyses the spatial correlation in data to produce equiprobable estimates (realizations) of each particular grid in the DEMs.…”
Section: Introdctionmentioning
confidence: 99%